Chemical variation of five natural extracts by non-polar solvent - Prayitno, T. A.; Widyorini, R.; Lukmandaru, G. (Maderas. Ciencia y Tecnología, 2020)
Chemical compounds of wood preservation from plants vary and are not known specific to the species. Chemical analysis of plants is responsible to ensure active compound in natural extracts wood treatment. There are many sources of natural extracts found in Indonesia that were explored for wood preservatives chemicals. They are bark of acacia and alstonia, leaves of orthosiphon and azardirachta and Dioscorea tubers. The present study was aimed at investigating the variation of the chemical constituent of natural extracts material of wood preservative through GC-MS analysis. Five natural extract sources were acacia bark (Acacia spp.), pulai bark (Alstonia scholaris), kumis kucing leaves (Orthosiphon spp.), mimba leaves (Azardirachta indica), and gadung tubers (Dioscorea spp.). Two non-polar solvents, i.e., n-hexane and petroleum ether were used for five natural source extractions following ASTM soxhlet extraction. The research showed that triterpene and fatty acid derivatives were the major compounds present in five natural extracts. They were lupeol; 7,22-Ergostadienone; Lup-20(29)-en-3-one; Lup-20(29)-en-3-ol, acetate, (3.beta.)-; urs-12-en-3-one; ethanol,2,2-diethoxy-; stigmasta-5,22-dien-3-ol, acetate,(3.beta.)-; 5H-3,5a-Epoxynaphth(2,1-c)oxepin, dodecahydro-3,8,8,11a-tetramethyl-; linoleic acid; naphthalene, 1-methyl-. These compounds have been assigned as the possibly responsible to against termites or fungi.